User Satisfaction on Zoom Application in Online-Based Student Learning Using Webqual - Indira RACHMAWATI; Dinda Riska AULIA (International Journal of Environmental, Sustainability, and Social Science, 2025)
One of the impacts of the COVID-19 pandemic has affected the education system and economy worldwide. The learning crisis in Indonesia at the beginning of the Covid19 pandemic has resulted in the suspension or closure of schools for an indefinite period. Students at the college and university levels are students who must be required to be able to carry out teaching and learning activities amidst the increasingly widespread spread of the corona virus (Covid19). Amid the Covid19 pandemic, all schools in Indonesia are implementing Work or Study from Home by conducting online learning using the Zoom application. This study aims to determine the satisfaction of using the Zoom application in online-based student learning using Webqual. This study uses a quantitative method and measures using the WebQual dimensions (Usability, Information Quality, Service Interaction) and user satisfaction variables. The data analysis technique uses descriptive with statistical calculations and causal data processing is carried out using multiple regression. The research data is in the form of a questionnaire distributed to 405 respondents who use the Zoom application. The results of the study show that the Webqual (X) variable consisting of Usability Quality (X1), Information Quality (X2) and Service Interaction (X3) has a positive and significant influence simultaneously on User Satisfaction on the Zoom Application.